The implementation of energy subsidy reduction policy on the Indonesian economy performance - Handayani, Rita; Juzilam, Siro; Daulay, Murni; Ruslan, Dede (International Journal of Financial, Accounting, and Management, 2020)
Abstract Purpose: This study aims to evaluate the impact of the implementation of the energy subsidy reduction policy conducted by the Government of Indonesia for the period 2015-2017. The author examines the application of the subsidy reduction policy and its impact on economic performance, specifically on economic growth; inflation rates, sectoral employment absorption, income levels and households group income distribution using the computable general equilibrium approach (CGE Model). Research Methodology: The study used data from the 2008 Social Economic Balance System (SNSE) published by the Indonesian Central Statistics Agency (BPS). Furthermore, it also built a balance of data base with the static version 1.1 PEP model, version 2.0 making the energy subsidy reduction policy a shock in the simulation model developed. Results: The author found that the application of policy to reduce energy subsidies has an impact on increasing economic growth, reducing inflation, increasing employment in the livestock, hospitality, land transportation and other service sectors. Limitation: The limitation of this study is the use of funding 2008. Contribution: The government as a stakeholder should provide the inclusive potential opportunity and considerable funds for research and development of new energy sources which will benefit of the future of nation's life.